SPEECH STYLE BY THE MAIN CHARACTERS IN THE ENOLA HOLMES MOVIE - Achmad, Winda Widiastuti; Sunra, La (Journal of English Literature and Linguistic Studies, 2023)
The purpose of this study is to identify the various linguistic idioms used in Nancy Springer's movie Enola Holmes. The descriptive approach used in this study According to Huberman and Miles (2014) (1994:10). The information was derived from Nancy Springer's film Enola Holmes, which depicts the lives of youths in the Victorian era. By seeing as many films as possible, data is analyzed. Make an effort to follow every discourse. The author groups a number of exchanges in the movie into categories to demonstrate the language style used in Enola Holmes and what the main character and other characters mean by language style in the context of the scene. friends and the author's linguistic style, Nancy Springer. The study's findings indicate that the following linguistic tenors are used in Nancy Springer's Enola Holmes: frozen, formal, relaxed, intimate, and consultative. Additionally, Nancy Springer's writing has a significant impact on the way language is generated, as it immediately conjures up an environment. And the conclusion of this study is that in the film Enola Holmes by Nancy Springer which depicts the environment of teenagers in the Victorian era, they prefer formal language styles in each language.